Dynamic spectrum access and coexistence experiences involving two independently developed cognitive radio testbeds - DOYLE, LINDA; NOLAN, KEITH EDWARD; SUTTON, PAUL DAVID (IEEE, 2007)
The Centre for Telecommunications Value-Chain Research (CTVR) and the Center for Wireless Telecommunications (CWT) are carrying out joint research work investigating the potential of different software-defined radio (SDR) and cognitive radio (CR) systems that can coexist in common frequency bands. This paper describes the independently developed dynamic spectrum access test beds used in a practical coexistence experiment. An initial analysis of actual coexistence experiences involving a primary user and a secondary opportunistic spectrum user in a common frequency band is also presented. The results in this paper include an analysis of a worst case scenario where the primary user and secondary opportunistic user are coexisting with no guard bands separating each other. The experimental results showed that the primary user experienced zero packet loss when guard bands separated the primary and secondary services. Additionally, when no guard bands were used and the spectrum segment was maximally used over the geographical area involved in the experiments, the signal to noise and interference ratio (SNIR) needed to be adjusted to 20 dB by modifying the secondary user transmissions in order to minimise the interference experienced by the primary user.
PUBLISHED
Keywords: Electronic & Electrical Engineering